1981
DOI: 10.1021/bi00521a016
|View full text |Cite
|
Sign up to set email alerts
|

Purification and characterization of Escherichia coli formamidopyrimidine-DNA glycosylase that excises damaged 7-methylguanine from deoxyribonucleic acid

Abstract: A DNA glycosylase that excises 7-methylguanines with alkali-opened imidazole rings (formamidopyrimidines) from DNA has been purified more than 8000-fold from Escherichia coli cell extracts. The enzyme does not cleave 3-methyladenine, uracil, and intact 7-methylguanine from DNA. In assays containing pyrimidine analogues like oxauracil, 2,4,6-triaminopyrimidine, 2,5,6-triamino-2-hydroxypyrimidine sulfate, formamidopyrimidine, and 5-nitroso-2,4,6-triaminopyrimidine, only the two compounds showed end product inhib… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

1
32
0

Year Published

1985
1985
2017
2017

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 74 publications
(33 citation statements)
references
References 41 publications
1
32
0
Order By: Relevance
“…An enzyme activity that cleaves 3' and 5' to this modified base, producing a single nucleotide gap in the modified strand, has recently been isolated from Escherichia coli (3). The general properties of this enzyme, designated 8-hydroxyguanine endonuclease, proved similar to those reported for the FPG protein of E. coli (4)(5)(6). The latter, also known as formamidopyrimidine (Fapy) DNA glycosylase, catalyzes release of imidazole ring-opened forms of guanine and adenine from alkylated or irradiated polynucleotides and DNA (4)(5)(6)(7)(8).…”
supporting
confidence: 76%
See 2 more Smart Citations
“…An enzyme activity that cleaves 3' and 5' to this modified base, producing a single nucleotide gap in the modified strand, has recently been isolated from Escherichia coli (3). The general properties of this enzyme, designated 8-hydroxyguanine endonuclease, proved similar to those reported for the FPG protein of E. coli (4)(5)(6). The latter, also known as formamidopyrimidine (Fapy) DNA glycosylase, catalyzes release of imidazole ring-opened forms of guanine and adenine from alkylated or irradiated polynucleotides and DNA (4)(5)(6)(7)(8).…”
supporting
confidence: 76%
“…Purines undergo opening of the imidazole ring to create Fapy residues (18) or are hydroxylated at the C-8 position to form 8-oxodG and 8-oxodA (1,19). Imidazole ring-opening is facilitated by alkylation at N-7, followed by treatment with alkali, resulting in DNA containing Me-Fapy (5,8,20).…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…In a recent study (5), the transformation of primary breast tumors to the metastatic state was shown to involve a Ͼ2-fold increase in ⅐OH damage in DNA, as indicated by modified nucleotide base models comprising mutagenic 8-hydroxyadenine (6) and the putatively nonmutagenic ring-opened product 4,6-diamino-5-formamidopyrimidine (fapyadenine; refs. [7][8][9][10][11]. In addition, plots of the modified nucleotide base model log 10 (fapyadenine͞8-hydroxyadenine) versus the size of metastatic and nonmetastatic breast tumors revealed that the metastatic tumor DNA had significantly greater structural diversity than the nonmetastatic tumor DNA (P ϭ 0.01; ref.…”
mentioning
confidence: 99%
“…It is eliminated from DNA by several mechanisms: spontaneous release by hydrolysis of the glycosylic bond, removal by TagH type enzymes, and opening of the im idazole ring (alkali-catalyzed) to produce 2,6-diamino-4-hydroxy-5N methylformamidopyrimidine (FAPY). An enzyme has been purified from E. coli (6,88) that removes FAPY as well as the adenine y-radiation product, 4,6-diamino-5-formamidopyrimidine (89) by a glycosylase action. This en zyme of Mr = 30,000 is specific for formamidopyrimidine in dsDNA.…”
Section: Formamidopyrimidine-dna Glycosylasementioning
confidence: 99%